Development of a health-related lifestyle self-management intervention for patients with coronary heart disease - Fernandez, R.; Davidson, Patricia; Griffiths, R.; Juergens, C.; Salamonson, Y. (Elsevier, 2009)
Risk-factor modification after an acute coronary event is imperative, and intervention strategies are continuously being developed to assist patients with behavioral change and, consequently, decreasing the risk of further coronary episodes. This article describes the development of the health-related lifestyle self-management (HeLM) intervention, which is a brief structured intervention embedded within the transtheoretical model of behavioral change. The HeLM intervention was developed by undertaking three discrete yet interrelated studies and consisted of the following components: goal-setting, the HeLM booklet, feedback regarding personal risk, team-building and communication with the patient's family physician, three supportive telephone calls, trained interviewers, a refrigerator magnet, and a health diary for self-monitoring. The HeLM intervention has been successfully implemented in 50 patients with acute coronary syndrome after discharge from hospital and has been demonstrated to be feasible and practical and could easily be delivered by health care professionals.